A new species of the genus Micryletta (Anura, Microhylidae) from Hainan Island, China - Yang, Jian-Huan (Science Press, 2021)

(untitled) (Zool Res)
We report on a new amphibian species of the genus Micryletta from Hainan Island, China, based on morphological and molecular analyses. The new species, Micryletta immaculata sp. nov., is diagnosed by a combination of the following morphological characters: medium-sized within genus (SVL 23.3–24.8 mm in males, n=3; 27.7–30.1 mm in females, n=2); dorsum bronze brown to reddish brown in life; dark brown spots and stripes on dorsum and flank absent; flanks largely pigmented with silver white; throat in adult males dark brown; undersides without dark patterns; outer metatarsal tubercle absent; supratympanic fold distinct; webbing between toes basal and poorly developed; tibiotarsal articulation adpressed limb reaching level of tympanum. The new species is divergent from all other congeners based on 16S rRNA gene sequences (3.0%–7.7%). Data on the natural history and male advertisement calls of the new species are provided. Following the IUCN Red List Categories and Criteria, we propose the new species to be listed as Vulnerable B1ab (iii).